ChemInform Abstract: Glyoxylic Acid in the Reaction of Isatoic Anhydride with Amines: A Rapid Synthesis of 3‐(Un)substituted Quinazolin‐4(3H)‐ones Leading to Rutaecarpine and Evodiamine. Issue 15 (April 2015) - Rao, K. Raghavendra; Raghunadh, Akula; Mekala, Ramamohan; Meruva, Suresh Babu; Pratap, T. V.; Krishna, T.; Kalita, Dipak; Laxminarayana, Eppakayala; Prasad, Bagineni; Pal, Manojit
Abstract: Glyoxylic acid (II) serves as a reactant and the catalyst, thus playing a dual role in this novel and robust metal‐free reaction.